Penggunaan Metode Forensik Dalam Pengungkapan Kejadian Klaim Asuransi Kebakaran - Ferdinand, Sean Michael; Awaloedin, Mulawarman; Nasyubun, M (JNANALOKA, 2023)
When an insurance claim occurs, there is often a difference of opinion between the insurer and the insured in interpreting the contents of the policy. In order to resolve claim disputes, according to the clauses in the policy, an opinion from an independent third party is needed. The purpose of third party involvement is to provide an opinion from another point of view. In this research, it is described how third parties are involved in resolving an insurance claim. Starting from the incident report, it was reported that a fire had occurred at latitude coordinates 7°25'26"S and longitude 112°43'33"E. Appointed investigators visit places affected by the fire to carry out inspections at the scene and investigate the origin of the fire and look for possible causes of the fire. Using forensic methods that include on-site investigation, damage analysis, witness statements, interpretation, and deductive reasoning processes,  data collected in the field is then analyzed to be tested against a number of proposed hypotheses. Debris and electrical cable samples were collected for further analysis. Based on physical evidence collected during the investigation, it was discovered that the fire started in the northwest portion of the building. The results of the findings were then traced by tracing the parts of the building that were damaged, and investigators found an electrical short circuit  due to a failure in the lights. These findings are then analyzed by the insurance claims team to determine the amount of the claim that must be paid by the insurer. There were no suspicious elements or circumstances surrounding the fire and other possible causes of the fire have been considered and ruled out.